Waldenström Macroglobulinemia and Cerebral Venous Thrombosis: From Diagnosis to Complication - Paulo Zoé Costa; Pedro Chorão; Andreia Póvoa; Pedro Vieira; Heidy Cabrera; Orlando Mendes; Céu Evangelista (Case Reports in Medicine)
Waldenström macroglobulinemia (WM) is a type of non-Hodgkin lymphoma in which cancer cells produce large amounts of an abnormal protein that can cause hyperviscosity syndrome (HVS). A 43-year-old woman with WM, who developed seizures, had a head computed tomography scan that showed signs of cerebral venous thrombosis (CVT). Nevertheless, the value of immunoglobulin M was lower than 50 g/L, and evaluation of serum viscosity was not performed. Moreover, there was no history of bleeding, and the eye funduscopy was normal. These findings lead to think of causes of CVT other than HVS in a patient with WM.